The Spread of The Hanafi School in The Period of Movarounnahr and The Important Services of Its Fukhis (Eurasian Journal of Humanities and Social Sciences, 2026)
The Hanafi school of thought first emerged in the city of Kufa. It was founded by Abu Hanifa, may God have mercy on him. For this reason, this school is called the "Hanafi" school. Although the Hanafi school of thought entered Transoxiana in the 8th-9th centuries, the most valuable works within the school were written between the 10th and 13th centuries. During this period, the jurists of the school made a wide range of great services to the Hanafi school of thought. Although their original origin was not Arabic, their works were written in Arabic. This indicates that they had thoroughly mastered almost all the sciences of Islam. Some of the jurists wrote in prose, while others wrote in verse. This indicates that the jurists of Transoxiana were well-versed in the science of jurisprudence. In this article, we will cover this topic in detail!